Preparation of a Doxorubicin Conjugate with (Co) Polymers of Methacrylic acid for Targeted Tumor Therapy - Olga Zhukova, Svetlana Bulgakova (Journal of Applied Pharmaceutical Science, 2016)
This study was performed in order to creation of a doxorubicin conjugate with methacrylic acid (co)polymers for targeted tumor therapy. Poly(t-butylmethacrylate) with the optimal for biocompatible polymers molecular-weight characteristics (Mn= 12,400; Mw/Mn = 1.35) was synthesized by radical polymerization in the presence of thioglycolic acid as a chain transfer agent. The obtained polymer was converted by acid hydrolysis into a water-soluble copolymer of t-butylmethacrylate and methacrylic acid of 20:80 mass%, respectively. The copolymer of t-butylmethacrylate and methacrylic acid was modified with folic acid which has affinity for tumor cells. A conjugate of the copolymer with doxorubicin and also a conjugate with the folate vector were synthesized. Their formation was proved using elemental analysis and IR, UV, NMR spectroscopy. Thus, in the course of the study the conjugate of doxorubicin was synthesized, combining the drug and a vector for delivery of the drug. This compound is a promising, as it represents a new form of transport delivering a well-known and widely used anticancer agent doxorubicin.
Keywords: Polymeric drug carrier, copolymer of methacrylic acid and t-butylmethacrylate, doxorubicin, folate vector, UV-spectroscopy, IR-spectroscopy, NMR-spectroscopy.